Cooperative breeding and the emergence of multilevel societies in birds. (9th January 2022) - Camerlenghi, Ettore; McQueen, Alexandra; Delhey, Kaspar; Cook, Carly N.; Kingma, Sjouke A.; Farine, Damien R.; Peters, Anne
Abstract: Multilevel societies (MLSs), where social levels are hierarchically nested within each other, are considered one of the most complex forms of animal societies. Although thought to mainly occurs in mammals, it is suggested that MLSs could be under‐detected in birds. Here, we propose that the emergence of MLSs could be common in cooperatively breeding birds, as both systems are favoured by similar ecological and social drivers. We first investigate this proposition by systematically comparing evidence for multilevel social structure in cooperative and non‐cooperative birds in Australia and New Zealand, a global hotspot for cooperative breeding. We then analyse non‐breeding social networks of cooperatively breeding superb fairy‐wrens ( Malurus cyaneus ) to reveal their structured multilevel society, with three hierarchical social levels that are stable across years. Our results confirm recent predictions that MLSs are likely to be widespread in birds and suggest that these societies could be particularly common in cooperatively breeding birds. Abstract : In this article, we conduct the first comparative analysis of multilevel societies and test the hypothesis that multilevel societies could be particularly common in cooperatively breeding birds, as both conditions are favoured by similar ecological (environmental unpredictability) and social (high social viscosity) drivers. We then illustrate how many of these species are likely to be structured by analysing multi‐year social networks of cooperatively breeding superb fairy‐wrens ( Malurus cyaneus ). Our study confirms that multilevel societies are likely to be widespread in birds, that their presence may be predicted by similar conditions to those that favour cooperative breeding, and, therefore, that more studies on birds should be conducted during the non‐breeding season, an often neglected period.